Biomolecular Release from Alginate‐modified Electrode Triggered by Chemical Inputs Processed through a Biocatalytic Cascade – Integration of Biomolecular Computing and Actuation. Issue 3 (29th December 2017) - Okhokhonin, Andrey V.; Domanskyi, Sergii; Filipov, Yaroslav; Gamella, Maria; Kozitsina, Alisa N.; Privman, Vladimir; Katz, Evgeny
Abstract: Biocatalytic cascades involving more than one or two enzyme‐catalyzed step are inefficient inside alginate hydrogel prepared on an electrode surface. The problem originates from slow diffusion of intermediate products through the hydrogel from one enzyme to another. However, enzyme activity can be improved by surface immobilization. We demonstrate that a complex cascade of four consecutive biocatalytic reactions can be designed, with the enzymes immobilized in an LBL‐assembled polymeric layer at the alginate‐modified electrode surface. The product, hydrogen peroxide, then induces dissolution of iron‐cross‐linked alginate, which results in release process of entrapped biomolecular species, here fluorescently marked oligonucleotides, denoted F‐DNA. The enzymatic cascade can be viewed as a biocomputing network of concatenated AND gates, activated by combinations of four chemical input signals, which trigger the release of F‐DNA. The reactions, and diffusion/release processes were investigated by means of theoretical modeling. A bottleneck reaction step associated with one of the enzymes was observed. The developed system provides a model for biochemical actuation triggered by a biocomputing network of reactions. Abstract :